Efektivitas Strategi Card Sort dalam Pembelajaran IPA pada Siswa Kelas IV SD Muhammadiyah 10 Palembang - Piko Priando; Dian Nuzulia Armariena; Rury Rizhardi (Journal on Education, 2023)
This research is motivated by the fact that the application of this material has not been fully maximized and optimal, especially in science learning. And also students still have a lot of difficulties understanding learning material and solving problems a given problem, because in teaching and learning activities the teacher only uses direct learning (lectures) and is only fixated on textbooks. This study aims to determine the effectiveness of the card sort strategy in learning science in class IV SD Muhammadiyah 10 Palembang. In this study using experimental research methods. Experimental research "To experiment is to try, to look for, to confirm" means to try, seek and confirm. The researcher concludes that learning the card sort strategy is a learning model that is very suitable to be applied because it can invite students to play an active and creative role in the learning process. the control taught using the conventional model was 67.50 and the average posttest score of the experimental class taught using the card sort learning strategy was 70.00 with a difference of 4.5. This shows that the posttest average score of the experimental class taught using the card sort strategy in science learning is higher than the average value of the control class taught using the conventional model. Thus it can be concluded that there is a significant effectiveness of the card sort strategy in science learning for CLASS IV SD Muhammadiyah 10 Palembang on the material of style and motion.